ปฏิสัมพันธ์ระหว่างประเภทข้อมูลย้อนกลับเชิงโต้ตอบด้วยคอมพิวเตอร์กับระดับความสามารถทางฟิสิกส์ที่มีต่อพัฒนาการด้านความสามารถและอภิปัญญาในการแก้โจทย์ปัญหาทางฟิสิกส์ของนักเรียนมัธยมศึกษาปีที่ 4 - ธันยบูรณ์ ธัญลักษณ์มะระ (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
The purposes of this study were (1) to study the interactions between interactive computer-based feedback types (fade-out interactive feedback, fade-in interactive feedback, constant interactive feedback, and knowledge of correct response feedback) and physics ability levels (high, moderate, and low) on the growth of problem-solving ability and metacognition in physics of students, and (2) to compare the growth of problem-solving ability and metacognition in physics of students who received four different types of interactive computer-based feedback. Sample consisted of 73 tenth grade students. The research instruments were (1) physics-based problem-solving ability exercises delivered via computer systems, (2) physics-based problem-solving ability tests, and (3) physics-based problem-solving metacognition inventory. Quantitative data were analyzed by using descriptive statistics, relative gain scores, repeated measures ANOVA, one-way ANOVA, two-way ANOVA, whereas qualitative data were analyzed by using analytic induction. Results revealed that1. There was an interaction between interactive computer-based feedback types and physics ability levels on the growth of problem-solving ability in physics of students at the statistically significant level of .05. However, there was no an interaction between interactive computer-based feedback types and physics ability levels on the growth of metacognition in physics of students at the statistically significant level of .05.2. Students in the high ability level who received different interactive computer-based feedback types did not differ in the growth of problem-solving abilities in physics at the statistically significant level of .05. Students in the moderate ability level, who received fade-out interactive feedback and constant interactive feedback, as well as students in the low ability level, who received constant interactive feedback were better in the growth of problem-solving abilities in physics than those who received knowledge of correct response feedback at the statistically significant level of .05. All Students who received different interactive computer-based feedback types did not differ in the growth of metacognition in physics at the statistically significant level of .05.